Validation and adaptation of the Serbian adaptation of the Marijuana Effect Expectancies Questionnaire among adolescents - Čanković, Dušan; Dinić, Bojana; Bokan, Dalibor; Ukropina, Snežana; Čanković, Sonja (Vojnosanitetski pregled, 2025)
Background/Aim. Expectancies about the effects of cannabis have been related to the onset and frequency of its consumption. One of the most used instruments to measure cannabis effect expectancies is the Marijuana Effect Expectancy Questionnaire (MEEQ). The aim of this study was to determine the psychometric properties of the Serbian adaptation of the MEEQ among secondary school pupils. Methods. The retrospective study included 1,642 secondary school pupils (52.3% female) from the South Bačka District, Vojvodina, Serbia. In addition to the MEEQ, the Cannabis Use Intention Questionnaire (CUIQ) was also used, as well as a self-report measure of cannabis use. Results. The original six-factor MEEQ model showed the best fit indices with the following factors: Cognitive and Behavioral Impairment, Relaxation and Tension Reduction, Social and Sexual Facilitation, Perceptual and Cognitive Enhancement, Global Negative Effects, and Craving and Physical Effects. All MEEQ scales showed positive and expected correlations with the CUIQ scales, among which the highest correlation was with the Attitudes toward Consumption scale. Correlations with self-report cannabis use were significant for all MEEQ scales, except for Cognitive and Behavioral Impairment. Conclusion. The results suggested good psychometric properties of the Serbian adaptation of the MEEQ. The results also confirmed the originally proposed factor structure, good reliabilities of the scales’ scores based on internal consistency, as well as convergent and criterion validity.